Implementation Handling of Children in Dealing With The Law in Polres Purworejo - Setio Raharjo (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
The purpose of this research is to investigate the implementation of the handling of children in conflict with the law in Polres Purworejo; 2) to know the constraints faced by police investigators in Polres Purworejo in performing their duties as investigator; and 3) to find solutions investigator in the face of constraints in the implementation of the handling of children in conflict with the law in Polres Purworejo. The method used in this research is empirical juridical approach or in other words the socio-juridical.Specifications research is descriptive. Data used in this study are primary data and secondary data. Methods of collecting data in this study using library study or library research. Analysis of the data used is qualitative data. The study states that 1) in order to organize the protection of women and children who are victims of crime and law enforcement against perpetrators, Unit Women and Children (PPA) Police have implemented procedures in accordance with the regulations stipulated in the mennangani children behadapan with the law; 2) there are two obstacles that arise in the implementation of minimum service standards in Women and Children Services Unit (PPA) Polres Purworejo, namely internal and external obstacles; 3) the efforts undertaken to overcome existing obstacles, including by conducting education and training for members of the PPA good Unit investigator, investigator helpers and staff who are in the PPA Unit to strengthen Human Resources.Keywords: Investigation; Children; Conflict with the Law.